Illocutionary Act Found in Movie “Nimona” - Ni Made Ariasih; Komang Dian Puspita Candra (RETORIKA: Jurnal Ilmu Bahasa, 2025)
Illocutionary act is a way of someone to utter something with intended meaning or purpose behind it. This research aimed to find out the type of illocutionary act that is uttered in a movie titled “Nimona”. Searle’s theory was applied in this research, which is types of illocutionary acts. The movie was chosen as a data source because the researcher was interested in the movie plot and the characters unique direct and indirect expression of illocutionary act. The studies were needed to offer a deeper understanding about what type of illocutionary act was found in the movie and about the movie plot that shown a various of unique expressions that was delivered by the characters. The result of the discussion showed that all the illocutionary acts were found throughout the movie. The researcher found 74 data points in total after observing the movie and script, the most data that were found was expressive illocutionary act. There are 3 data of declarative, 1 data of assertive, 41 data of expressive, 25 data of directive, and 4 data of commissive.